The Hazards and Rewards of Screening Using a Population Register: The Case of HAGIS - Bell, David; Douglas, Elaine (International Journal of Population Data Science, 2019)
This paper focuses on the sampling mechanism used to generate the pilot for the HAGIS (Healthy AGeing In Scotland) study. HAGIS is the Scottish equivalent of ELSA in England and HRS in the US. The sample for the HAGIS pilot was screened using a Scottish population register - the National Health Service Central Register (NHSCR). It is used to identify individuals who use NHS services in Scotland. Each individual using NHS resources is allocated a unique identifier, known as a Community Health Index (CHI) number. CHI numbers form a database which is effectively a population register for Scotland. CHI numbers have not previously been used to screen a sample for a social survey. Our paper describes the steps involved from obtaining permission to screen using CHI to handing set of addresses to a survey company tasked with approaching individuals and conducting a face-to-face interview. The paper goes on to illustrate the practical difficulties involved in achieving a high response rate from those approached and the compromises that were made to achieve the target sample size. It also discusses the consent rates that HAGIS achieved for linkage to administrative health data. The final section of the paper outlines the advantages of combining administrative data linkage with screening using a population register. It illustrates this by comparing various health characteristics of consented survey respondents with those of the original randomly drawn sample from the NHSCR. These comparisons facilitate testing of hypotheses that consented sample respondents comprise an unbiased sample from the Scottish population across a variety of health dimensions. The paper concludes with a discussion of the implications of these hypothesis tests and the more general benefits of sample screening using a population register and administrative data linkage.